Great Contemporary Pianists Speak for Themselves - Mach, Elyse (New York Dover publications, 1991)
Fascinating interviews with 25 renowned pianists: Ashkenazy, Badura-Skoda, Bolet, Brendel, de Larrocha, Gould, Horowitz, Ohlsson, Tureck, Watts, 15 more. Revealing, candid thoughts about themselves, their careers, music they play, life of a concert pianist. "Mach's interviews will enhance the pleasure of any concertgoer." People. Introduction by Sir Georg Solti. Includes 51 black-and-white photographs.
Keywords: Arrau, Claudio -- 1903-1991; Brendel, Alfred -- 1931-2025; Gould, Glenn -- 1932-1982; Past; Biography; Music history